Issues Relating to Staff Training Hospitality Industry: A Case Study of Premier Hotel, Ibadan, Oyo State, Nigeria - Adeniji, Paulina Olufunke (Journal of Home Economics Research (JHER)., 2021)
The general objective of the study was to investigate the issues relating to staff training in Hospitality industry using Premier Hotel Ibadan as a case study. Specifically, the study determined: practices employed by management of Premier Hotel in training their staff, and staff expressed benefits of their own training. Design of the study was survey. Area of study was Premier Hotel Ibadan, Oyo State, Nigeria. Population for the study comprised of all staff (both skilled and unskilled) in Premier Hotel, Ibadan. Instrument for data collection was questionnaire. Data were analysed using frequency, percentage and mean. Major findings include that most strategy training employed by the Management of Premier Hotel in training their staff is on– the job training (55%), most targeted for training were the new staff (45%), half (49.5%) of the respondents were trained on a monthly basis. There are 10 skills areas in which training are given. Other findings include nine staff expressed benefits of training. These including that training enhance staff performance in the hotel, makes staff career path to be more focused, improves the social circle of the employee, and others. Based on the findings, it is recommended that the hospitality industry, particularly hotels, should endeavour to train their staff regularly in order to upgrade competency, and staff commitment in the hotel industry.
Keywords: Issues; Hospitality; industry; Benefits; Training; Staff; Premier Hotel